Women's leadership training in political contestation for the Muhammadiyah student association at Takalar Regency - Andriana Andriana; Sitti Rahmawati Arfah; Nur Wahid; Syukri Syukri; Nur Apriani Nur (Community Empowerment, 2024)
This service activity aims to increase women's knowledge and leadership skills in political contestation. The method used in this activity is carried out in three stages, namely 1) preparation by socializing the activity to the community, 2) implementation is carried out by means of training, and 3) evaluation is carried out by distributing pre-test and post-test questionnaires to measure the level of knowledge and skills of partners regarding the leadership training of women in political contestation that has been carried out. The results of this service show that cadres have increased their knowledge and skills regarding women's leadership training with a percentage of 93.21% in the good category. This shows that there are differences in the level of community knowledge after being given women's leadership training which is increasing.